Logistics implications on consumers' trust and satisfaction: consumer's repurchase intention in C2C marketplaces based in Singapore - Ting, Clara Jie Lyn (Nanyang Technological University, 2023)
With the rising popularity of Consumer-to-Consumer (C2C) marketplaces, there is a need to conduct a study on the perspective of these consumers for businesses to thrive. In order to obtain more specific and valuable insights for C2C marketplaces, we narrowed the study down to the most popular product category which is fashion apparels. However, differing from Business-to-Consumer (B2C) e-commerce stores, C2C requires these individual sellers or buyers to arrange their own logistics transport for the goods sold. Unlike B2C marketplaces whose logistics are usually outsourced, these sellers or buyers may not have the expertise in logistics transport for their own goods, which makes it harder for them to assure the quality in logistics services. This study aims to assess how the logistics service providers may potentially affect the consumers’ repurchase intention towards the C2C marketplace. The study was conducted using empirical data (N=104) and statistical software SmartPLS through PLS-SEM. Based on our findings, it can be suggested that logistics service providers (LSPs) positively impact consumer satisfaction and consumer trust which indirectly affects consumer’s repurchase intention. To be specific, findings have shown very high correlation between consumer trust and quality of logistics services. Furthermore, consumer’s trust has a higher correlation with consumer’s repurchase intention as compared to consumer’s satisfaction. However, other than the logistics service, we have conducted an analysis on how demographics may potentially affect consumer’s repurchase intention. As this study was conducted solely in the context of Singapore, we discovered new insights that considers the demographics in this multi-cultural society. We discovered certain characteristics of the population may have a correlation with the consumer’s behaviour. Such as age groups below 30 years old may have tendency for higher consumer repurchase intention. Overall, this study exemplifies the significance of LSPs in C2C context, specifically in a developed country like Singapore. It offers valuable perspectives for C2C marketplaces in understanding the consumers’ perspective to better accommodate their needs which enhances their competitiveness.